Analisis Bibliometric Job Crafting dan Agenda Penelitian di Masa Depan - Rina Dewi; Ilham Ilham; Bambang Karnaen P; Sugiarto Sugiarto (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Proactive job crafting behavior is a study that is of interest to writers or researchers to be explored more deeply in relation to human resource management practices. Using the bibliometric method supported by the Scopus search engine and illustrated using Vos Viewer software was used to answer research questions. The results of the research found that the quantity of productivity that had been carried out in previous research was 885 documents, the most productive researcher was Bakker AB with 57 documents, the source of the most documents was published in the Frontiers In Psychology journal with 40 documents, the most productive affiliate was Erasmus Universiteit Rotterdam with 77 documents , the most productive country is the Netherlands with 179 documents, the most document types are articles with 740, equivalent to 83.6%, the most research subject areas are Business, Management and Accounting 459, equivalent to 30.3%, five main networks of author collaboration, a research map consisting of five clusters main as well as document maps based on density. These findings increase the understanding of future researchers to explore in depth the influence of job crafting on other variables.